Integral Perspective on Happiness - Uotinen, Joonas (Approaching Religion, 2015)
A happiness science has emerged amidst, and spans, the social sciences. This research, despite the long philosophical tradition on happiness, is in its infancy and a robust theory of happiness is called for. I will review parts of the literature and some of the main happiness theories using Ken Wilber’s Integral approach. I will concentrate largely on Aristotle’s eudaimonia, as that has re-emerged into the centre of happiness discussions as a possible contender for the prevailing subjective happiness theories. The Integral approach seems to provide valuable insights into many happiness theories, juxtapose them in a comprehensible way, pinpoint deficiencies, and propose enhancements. Amongst other things, I will propose a new happiness theory combining John Kekes’ happiness theory with ecological ethics and I will conclude that enlightenment proves to be a good candidate for the ultimate good, or summum bonum, I will enlarge on Aristotle’s theory and propose that Wilber’s theory provides an ‘Integral road map towards eudaimonia enhanced – the enlightenment’. I will argue that eudaimonia and enlightenment, though superficially dissimilar, accord in surprising ways, to a great extent. I will discuss whether the discussion of happiness and morality is critically biased, and I will discuss the societal implications that Wilber’s conception of the human might have through its implications for happiness theories.